2010
DOI: 10.1016/j.physletb.2010.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Hard-gapped holographic superconductors

Abstract: In this work we discuss the zero temperature limit of a "p-wave" holographic superconductor. The bulk description consists of a non-Abelian SU (2) gauge fields minimally coupled to gravity. We numerically construct the zero temperature solution which is the gravity dual of the superconducting ground state of the "p-wave" holographic superconductors. The solution is a smooth soliton with zero horizon size and shows an emergent conformal symmetry in the IR. We found the expected superconducting behavior. Using t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 19 publications
6
91
0
3
Order By: Relevance
“…The general definition stated here should be useful in analyzing cases where we have spontaneous symmetry breaking in the boundary, particularly when these order parameters break rotational invariance [42]. We note that at zero temperature k F is strictly real and corresponds to the pole at ω = 0, but for non-zero temperatures the pole at ω = 0 is complex.…”
Section: B Non-equilibrium Dynamics At the Fermi-surfacementioning
confidence: 98%
“…The general definition stated here should be useful in analyzing cases where we have spontaneous symmetry breaking in the boundary, particularly when these order parameters break rotational invariance [42]. We note that at zero temperature k F is strictly real and corresponds to the pole at ω = 0, but for non-zero temperatures the pole at ω = 0 is complex.…”
Section: B Non-equilibrium Dynamics At the Fermi-surfacementioning
confidence: 98%
“…Non-trivial holographic RG flow for some components of the shear viscosity tensor has also been reported in other anisotropic systems with gravity dual. Recent work [32], in anisotropic superfluids [17], has shown that the holographic RG flow of some components of the shear viscosity tensor is non-trivial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to study the holographic shear viscosity [5][6][7][8], holographic superconductors [9,10] and holographic (non)fermi-liquids [11][12][13]. In this paper, we will focus on the holographic p-wave superconductors [14][15][16].…”
Section: Introductionmentioning
confidence: 99%